Industrial solvents handbook - Flick, Ernest W. (Noyes Data Corp., 1998)
Completely revised, and vastly expanded, this 5th Edition is a well-established and successful reference volume designed principally for the chemical and other process industries, but will be found useful by anyone needing the latest pertinent data on industrial solvents. The over 1,200 tables in this book contain basic data on the physical properties of most solvents and on the solubilities of a variety of materials in these solvents.